Computational Fluid Dynamics-The Futuristic Innovation in Pharmaceutical Industry - N, Lavanya; Bhattacharyya, Sayani (Indian Journal of Pharmaceutical Education and Research, 2021)
The review provides an insight into the application of Computational Fluid Dynamics (CFD), a versatile tool for analysis of complex dynamics of air and fluid flow in pharmaceutical operations. The principle of Navier Stokes equation on the explanation of the mathematics on flow of material is outlined in the review. Using the mathematical equations generation of a computer simulated model helps to develop a process, design a device and an operation by fusion of their theoretical background and experimental validation. The use of CFD is gaining importance in the pharmaceutical field as it can trace the critical minor change that leads to a significant impact in the process development. The simulation concept can be useful in terms of identifying and controlling the hazards of these operations on product damage. An outcome of an optimized process, device or operation can be beneficial in each stage of product development and quality build-up. The application of CFD in the development of inhalers, drying process and hydrodynamics of dissolution apparatus is focused here.
Keywords: Computational fluid dynamics; Navier Stokes equation; Inhaler device; Drying process; Dissolution